2003
DOI: 10.1002/bmb.2003.494031020193
|View full text |Cite
|
Sign up to set email alerts
|

On the convenience of using a computer simulation to teach enzyme kinetics to undergraduate students with biological chemistry‐related curricula

Abstract: Enzyme kinetics is a difficult subject for students to learn and for tutors to teach. During the practicals included in the biochemical courses at the Faculty of Chemistry of Universidad Nacional Autó noma de Mé xico, we found that the students acquire good training in the calculations to obtain kinetic parameters such as K m , V max , optimum pH, etc., but, when they are questioned about the significance of the values and their relationship to enzyme catalysis, many confusing ideas arise. To provide extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 3 publications
2
23
0
1
Order By: Relevance
“…And yet other studies, e.g. González-Cruz et al (2003) and Mosalanejad et al (2012) have found benefits for a guided or semi-guided approach over a fully unguided exploration of a teaching simulation. Students themselves have been found to have widely varying opinions about the effectiveness of student-centred learning (Lea et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…And yet other studies, e.g. González-Cruz et al (2003) and Mosalanejad et al (2012) have found benefits for a guided or semi-guided approach over a fully unguided exploration of a teaching simulation. Students themselves have been found to have widely varying opinions about the effectiveness of student-centred learning (Lea et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Teaching practices that accompany interactive simulation models further impact the development of student knowledge and understanding (McKagan, Handley, Perkins, & Wieman, ). For instance, González‐Cruz, Rodríguez‐Sotres, and Rodríguez‐Penagos () showed that students who were involved in a semi‐guided group learned more about enzyme kinematics from a simulation than those who were in an unguided group. Often, teachers need to determine the best ways to support students as they interrogate models, enabling them to make sense of model output and identify limitations of modeling (NGSS Lead States, ; Weintrop et al, ; Wilkerson‐Jerde & Wilensky, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional classroom, the abstract manner of comparing keys, locks, and graphing double reciprocal plots diminishes most students’ enthusiasm for learning these important concepts. As a result, Gonzales‐Cruz and others () proposed and tested different approaches to increase students’ understanding of K m , V max and optimizing the enzyme reaction conditions such as pH. They developed a computer software simulation and found the students performed best when they were allowed to retain the majority of the control for their learning.…”
Section: Introductionmentioning
confidence: 99%